Application of decellularized vascular matrix in small-diameter vascular grafts - Li, Yuanming; Zhou, Ying; Qiao, Weihua; Shi, Jiawei; Qiu, Xuefeng; Dong, Nianguo (Frontiers in Bioengineering and Biotechnology, 2023)
Coronary artery bypass grafting (CABG) remains the most common procedure used in cardiovascular surgery for the treatment of severe coronary atherosclerotic heart disease. In CABG, small-diameter vascular grafts can potentially replace the vessels of the patient. The complete retention of the extracellular matrix, superior biocompatibility, and non-immunogenicity of the decellularized vascular matrix are unique advantages of small-diameter tissue-engineered vascular grafts. However, after vascular implantation, the decellularized vascular matrix is also subject to thrombosis and neoplastic endothelial hyperplasia, the two major problems that hinder its clinical application. The keys to improving the long-term patency of the decellularized matrix as vascular grafts include facilitating early endothelialization and avoiding intravascular thrombosis. This review article sequentially introduces six aspects of the decellularized vascular matrix as follows: design criteria of vascular grafts, components of the decellularized vascular matrix, the changing sources of the decellularized vascular matrix, the advantages and shortcomings of decellularization technologies, modification methods and the commercialization progress as well as the application prospects in small-diameter vascular grafts.